A Systematic Review on the Influences of Neurotoxicological Xenobiotic Compounds on Inhibitory Control - Perez-Fernandez, Cristian; Flores, Pilar; Sánchez-Santed, Fernando (Frontiers in Behavioral Neuroscience, 2019)
Background. Impulsive and compulsive traits represent a variety of mal-adaptative behaviors defined by the difficulties to stop an improper response and the control of a repeated behavioral pattern without sensitivity to changing contingencies, respectively. Otherwise, human beings are continuously exposed to plenty neurotoxicological agents which have been systematically linked to attentional, learning and memoristical dysfunctions, both preclinical and clinical studies. Interestingly, the link between both impulsive and compulsive behaviors and the exposure to the most important xenobiotic compounds have been extensively developed; although the information has been rarely summarized. For this, the present systematic review schedule and analyze in depth the most important works relating different subtypes of the above-mentioned behaviors with 4 of the most important xenobiotic compounds (Lead, Methylmercury, Polychlorinated biphenyls and Organophosphates) in both preclinical and clinical models. Methods. Systematic search strategy on PubMed databases was developed, and the most important information was structured both in text and in separate tables. Results. All the compounds have an important empirical data which supports their role in the modulation of inhibitory control, with stronger support in animal models. However, preclinical and clinical studies have systematically focused on different sub-types of the above-mentioned behaviors, as well as impulsive choice or habit conformations have been rarely studied. Discussion. The strong empirical support contrasts with the lack of connection between preclinical and clinical models. Further research should be focused on dissipate these differences as well as deeply study impulsive choice and decision making, both animals and humans.